Answer:
Correct option is C) x also increases 5 times .
Explanation:
Given:
y=7x
The above equation can be rewritten as
![x=(y)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kia30jjogb3bs9fu89qixbw4xn0g1kuwer.png)
Now, if we increase the y 5 times then we would have,
![x'=5*(y)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s837hi52bohko3ycrf7gzpdz3rcd795i4b.png)
Which is also equal to
x'=5x
Hence we can say that if we increase the value of y 5 times then we get that the value of x also increases 5 times.